Transitioning to Digital Currency: Factors Influencing Public Acceptance of the Digital Rupiah - Nusandika Patria; Made Harta Dwijaksara; Setiadi Yazid (Journal of Information Systems Engineering and Business Intelligence, 2026)
Background: The transformation of payment systems from cash-based transactions to digital platforms has significantly influenced the financial behavior of Indonesian society. A major innovation in this transition is the development of the Digital Rupiah, a Central Bank Digital Currency (CBDC) initiated by Bank Indonesia. Although global studies on CBDC adoption are emerging, limited research has examined its acceptance in Indonesia, particularly among technologically literate users, such as cryptocurrency customers. Objective: This study focuses on public acceptance of the digital rupiah and examines how trust and innovativeness serve as additional determinants beyond the core constructs of the UTAUT. Methods: A quantitative research design was employed using scanning electron microscopy-PLS. The study involved 400 respondents who are active Indonesian cryptocurrency users. The relationships between UTAUT variables and extended constructs were assessed using data derived from systematically designed questionnaires. Results: Performance expectancy, effort expectancy, social influence, trust, and innovativeness have a significant impact on behavioral intention to use digital rupiah, whereas facilitating conditions and behavioral intention directly influence use behavior. Importantly, the inclusion of trust and innovativeness as additional constructs revealed their substantial contribution in shaping attitudes and intentions toward adopting CBDC-based financial technologies. Conclusion: The following factors play vital roles in the acceptance of the digital rupiah. These insights provide valuable guidance for policymakers, particularly the Bank of Indonesia, in designing effective communication and socialization strategies to foster adoption. Future studies should further examine user acceptance across different demographic groups and broader segments of Indonesian financial technology users.   Keywords: Digital Rupiah, Central Bank Digital Currency (CBDC), UTAUT, Trust, Innovativeness, SEM-PLS